Model Platform Berbasis Mobile Untuk Manajemen Data Rekam Medis di Pos Pelayanan Terpadu Menggunakan Feature Modeling dan Unified Modeling Language - Ardianto, Darmawan; Noprisson, Handrie (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
As one of the Posyandu, Chica II also provides medical record data for the community. However, the management of this data often faces challenges, such as manual recording, unorganized data, and difficulty in accessing information quickly. This study aims to develop a mobile-based platform model for managing medical record data in Posyandu. The system development uses the waterfall methodology, which includes the stages of requirement analysis, design, implementation, and testing. The system is implemented using Java programming with MySQL as the database, developed through Android Studio using a native approach. The results of the study indicate that the developed system includes key features such as registration management, user management, health monitoring, mapping, reporting, and education. The system is also integrated with a previously developed web-based system, enabling comprehensive data management, including managing child data, immunizations, weighing records, and user management, designed to meet the operational needs of Posyandu.